2021
DOI: 10.1055/a-1482-2343
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Use of Natural Products against Developmentally Programmed Metabolic Syndrome

Abstract: Parental dietary choices and/or nutritional interventions in the offspring are critical to early life development, especially during the periods of active developmental plasticity in the offspring. Exposure to a high-fructose, high-fat diet during the fetal or neonatal period predisposes the affected individuals to the development of one or more features of metabolic syndrome, such as dyslipidemia, insulin resistance, diabetes, and associated cardiovascular diseases, later in their life. Owing to the increasin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 114 publications
0
2
0
Order By: Relevance
“…With a greater understanding on the mechanisms underlying MetS programming, the development of mechanism-targeted strategies holds potential for reprogramming. So far, strategies to offset underlying mechanisms governing MetS that have been evaluated range from avoidance of risk factors, nutritional interventions, pharmacological therapies, exercise, to lifestyle modification [6][7][8][9]81,161,162].…”
Section: Reprogramming Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…With a greater understanding on the mechanisms underlying MetS programming, the development of mechanism-targeted strategies holds potential for reprogramming. So far, strategies to offset underlying mechanisms governing MetS that have been evaluated range from avoidance of risk factors, nutritional interventions, pharmacological therapies, exercise, to lifestyle modification [6][7][8][9]81,161,162].…”
Section: Reprogramming Strategymentioning
confidence: 99%
“…Several phytochemicals with antioxidants have been reported to have beneficial effects against major hallmarks of MetS in adult offspring [161]. A previous report showed that early postnatal administration of oleanolic acid prevented dyslipidemia and insulin resistance in adult rat offspring [165,166].…”
Section: Antioxidantsmentioning
confidence: 99%